Assessment of knowledge, Attitude and practice of the local community on watershed management at Kindo Koysha Woreda of Wolayta Zone, Southern Ethiopia - Gebretsadik, Teklu; Debara, Mekonen (International Journal of Agriculture, 2017)
Purpose: The objective of the study is to identify the factors influencing knowledge, Attitude and practice of the local community on watershed management. For this, raising the awareness and enabling of the community at large and specifically farmers' at Woreda level providing short and long term training and education are required until they reach sustainability and to develop sense of ownership in the development practices Thus there is a need to take action to protect the environment and introduce sustainable use of resource. The action to be taken, however, has to be supported by the community who should participate in the environment protection activities. Thus, Comprehending the driving factors of farmers' participation in watershed development is crucial to improve the response mechanisms related to sustainable management of natural resource in the study area. However, research work on farmers' participation on watershed development is limited in study area. The extents of farmers' participation on watershed development and factors that influence watershed development are not well identified. Method: A purposive sampling procedure was applied to select two kebeles and 80 sample respondents. Data were collected from both primary and secondary sources. The methods of data collection employed include sample survey by administering an interview schedule and focus group discussions. Results: Results of Order Logit model showed that age, education level of respondents, sex, family size, farm size, extension service and training were positively and significant related to farmers' participation. On the other hand, distance to watershed and dependence ratio were negative and significant related to farmers' participation on watershed development at different probability levels. Results of this research and other observations revealed that watershed development activities could only be successful with active participation of the community. Policy recommendation: Government and other concerned body should design necessary strategies to empower women to participate equitably with man in watershed development. Strengthening the capacity of females through formal and informal education (like literacy) should be also an integral part of the whole development process.